Bibliography on Cold Regions Science and Technology. Volume XXV, Part 1. - COLD REGIONS RESEARCH AND ENGINEERING LAB HANOVER N H (1971)
The volume contains material accessioned between July 1970 and June 1971. Pt. 1 contains the full citation of over 4300 items, in many cases with abstracts. (Author) See also Volume 24, Part 1, AD-715 769 and Volume 25, Part 2, AD-740 202.